Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1074/jbc.m112.412742
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Chemokine-mediated Coalescence of Preformed Flotillin Hetero-oligomers in Human T-cells

Abstract: Background: Coexpression of the membrane microdomain-associated proteins flotillin-1 and -2 is required for their location in uropods of chemokine-stimulated T-cells. Results: Coexpression of untagged flotillin-2 in T-cells markedly enhances FRET between flotillin-1-EGFP and flotillin-1-mCherry. Conclusion: Our data strongly suggest predominant formation of flotillin hetero-oligomers in T-cells. Significance: This study enhances understanding of the molecular organization of T-cell uropod membrane microdomains. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 19 publications
5
19
0
Order By: Relevance
“…Note that these FRAP experiments were carried out at 20°C, as rapid shape changes and migration occurring at 37°C precluded accurate bleaching, acquisition and evaluation of FRAP data. The T cells were cotransfected with flotillin-1 and -2 tagged with mCherry as uropod markers (singly expressed flotillins do not cap, see Baumann et al, 2012) and bleaching of EGFP was carried out in the region of flotillin caps, if present. As shown in Table 1, 75% of T567D ezrin-EGFP is immobilized in cells not exposed to SDF-1, as compared to only 26% of WT ezrin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that these FRAP experiments were carried out at 20°C, as rapid shape changes and migration occurring at 37°C precluded accurate bleaching, acquisition and evaluation of FRAP data. The T cells were cotransfected with flotillin-1 and -2 tagged with mCherry as uropod markers (singly expressed flotillins do not cap, see Baumann et al, 2012) and bleaching of EGFP was carried out in the region of flotillin caps, if present. As shown in Table 1, 75% of T567D ezrin-EGFP is immobilized in cells not exposed to SDF-1, as compared to only 26% of WT ezrin.…”
Section: Resultsmentioning
confidence: 99%
“…Localized positive feedback loops and inhibitory effects of front signaling pathways on rear signaling and vice versa are thought to reinforce this biochemical and structural cell polarization (Bagorda and Parent, 2008). Specific proteins, including adhesion receptors, cytoskeletal proteins, and membrane-microdomain scaffolding proteins such as flotillin-1 and -2, have been shown to segregate to the uropod of polarizing T-lymphocytes (Sánchez-Madrid and Serrador, 2009; Affentranger et al, 2011; Baumann et al, 2012). Localized Rho activation in the rear results in uropod contraction and suppresses formation of protrusions; localized Rac activation in the front induces formation of F-actin-rich protrusions.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that high-order oligomerization and membrane-binding motifs artificially target cytosolic proteins to membrane patches, which accumulate at the lagging edge in polarized cells (48)(49)(50)(51)(52). Oligomerizing membrane microdomain components also enrich at the rear of polarized neutrophils or T cells (53)(54)(55)(56)(57). The WD40 domain enhances the stability and immobility of CynA at the lagging edge, either through oligomerization alone or by interaction with other proteins, as evidenced by the differences between CynA 1-574 and either CynA or the tandem PH domain, CynA 1-204+1-204 .…”
Section: Discussionmentioning
confidence: 99%
“…The uropod is a plasma membrane protrusion that contains specific organelles along with cytoskeletal, adhesion and signaling proteins (Serrador et al, 1997; Sánchez-Madrid & Serrador, 2009). Flotillins, membrane microdomain scaffolding proteins, are also enriched in leukocyte uropods and are involved in uropod formation (Rossy et al, 2009; Ludwig et al, 2010; Affentranger et al, 2011; Baumann, Affentranger & Niggli, 2012). Recent in vivo data using inhibition of uropod formation by suppressing Rho-kinase activity suggest that the uropod is especially important for T cell migration through constricted spaces (Soriano et al, 2011).…”
Section: Introductionmentioning
confidence: 99%